Real Estate Agency Practice in Malaysia: Future Direction - Zarita Ahmad @ Baharum,; Ting Kien Hwa,; Sharuzaman Mohd Saleh, (2024)
This book is the culmination of extensive research, practical insights and foresight into the evolving landscape of real estate practices in Malaysia. As the industry continues to adapt to changing market dynamics, technological advancement and regulatory developments, it has become imperative for real estate professionals to stay ahead of the curve.In this book, we delve into the current state of real estate agency practices in Malaysia and provide a comprehensive analysis of the trends shaping the future of the industry. From digital transformation and sustainable development to evolving consumer preferences, we explore the diverse factors influencing the direction of real estate agencies in Malaysia.We sincerely hope this book serves as a valuable resource for all vested in the future of real estate in Malaysia and inspires proactive strategies that will drive the industry forward. Embark with us on this journey imto the heart of Malaysian real estate, as we collectively envision and chart the path for a resilient, ethical and prosperous future.